2021
DOI: 10.3390/plants11010008
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Resequencing of Near-Isogenic Lines Reveals a Genomic Region Associated with High Trans-Lycopene Contents in Watermelon

Abstract: Trans-lycopene is a functional phytochemical abundant in red-fleshed watermelons, and its contents vary among cultivars. In this study, the genetic basis of high trans-lycopene contents in scarlet red flesh was evaluated. Three near-isogenic lines (NILs) with high trans-lycopene contents were derived from the scarlet red-fleshed donor parent DRD and three coral red-fleshed (low trans-lycopene contents) recurrent parents. The lycopene contents of DRD (589.4 ± 71.8 µg/g) were two times higher than that of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…The b-carotene and lycopene of F 2 individuals were extracted from freeze-dried watermelon flesh according to the method described by Lee et al (2022). Briefly, 0.1 g of finely crushed watermelon sample was added to 1 ml of ethanol containing 0.5 mM butylated hydroxytoluene and mixed carefully.…”
Section: Fruit Phenotype Analysismentioning
confidence: 99%
“…The b-carotene and lycopene of F 2 individuals were extracted from freeze-dried watermelon flesh according to the method described by Lee et al (2022). Briefly, 0.1 g of finely crushed watermelon sample was added to 1 ml of ethanol containing 0.5 mM butylated hydroxytoluene and mixed carefully.…”
Section: Fruit Phenotype Analysismentioning
confidence: 99%
“…KASP TM markers UGA3_10738714, UGA3_10795402, and UGA3_11016809, associated with the Qdff3-1 loci conferring early maturity in watermelon, have been developed for breeding [32]. CAPS markers CIR6-M1 and CIR6-M4 are linked to trans-lycopene content [103]. Pei et al [104] developed a KASP marker to identify pale green coloured watermelon flesh.…”
Section: Molecular Markersmentioning
confidence: 99%
“… Jin et al (2019) also suggested the development of a CRTISO gene-based marker for orange flesh with high prolycopene content. Recently, Li et al (2020) and Lee et al (2021) described the markers distinguishing scarlet and coral red. However, no markers have been reported for selecting incomplete yellow, which is essential for breeding canary yellow- or red-fleshed watermelons.…”
Section: Introductionmentioning
confidence: 99%
“…The WGRS of a large number of watermelon accessions and genome-wide association study (GWAS) revealed sequence polymorphisms and genes for fruit-related traits, such as fruit shape, flesh color, rind patterns ( Park et al, 2018 ; Subburaj et al, 2019 ), and disease resistances, including gummy stem blight ( Lee et al, 2018 ). The WGRS of near-isogenic lines successfully revealed a locus related to the high lycopene content in a scarlet red-fleshed watermelon cultivar ( Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%